2023
DOI: 10.1371/journal.pone.0284074
|View full text |Cite
|
Sign up to set email alerts
|

Damage and failure of underground subway stations under different soil constraint conditions

Abstract: Investigations from past earthquakes have shown that underground subway stations can suffer excessive deformation under strong seismic loads, leading to the damage of critical components and the collapse of structures. This study presents the results of finite element analyses on the seismic damage of underground subway stations installed under different soil constraint conditions. The plastic hinge distribution and damage characteristics of cut and cover double-storey and three-storey subway stations are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Tao et al [13] studied the seismic response law of Y-shaped columns by taking a large-span, double-deck subway station structure of Beijing Metro Line 6 as an engineering prototype; they found that the horizontal seismic response at the top of the forked branch of Y-shaped columns is stronger than in other parts, which manifests with larger stresses than in other parts. Zhang et al [14] considered the effect of different soil constraints on damage in subway stations. Significant differences in the development and distribution of flexural plastic hinges of underground structures with different soil-structure stiffness ratios were derived for the same level of interlayer displacement deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al [13] studied the seismic response law of Y-shaped columns by taking a large-span, double-deck subway station structure of Beijing Metro Line 6 as an engineering prototype; they found that the horizontal seismic response at the top of the forked branch of Y-shaped columns is stronger than in other parts, which manifests with larger stresses than in other parts. Zhang et al [14] considered the effect of different soil constraints on damage in subway stations. Significant differences in the development and distribution of flexural plastic hinges of underground structures with different soil-structure stiffness ratios were derived for the same level of interlayer displacement deformation.…”
Section: Introductionmentioning
confidence: 99%